2013
DOI: 10.1038/ncomms2402
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between myosin IIA-mediated contractility and actin network integrity orchestrates podosome composition and oscillations

Abstract: Tissue-resident dendritic cells patrol for foreign antigens while undergoing slow mesenchymal migration. Using actomyosin-based structures called podosomes, dendritic cells probe and remodel extracellular matrix topographical cues. Podosomes comprise an actin-rich protrusive core surrounded by an adhesive ring of integrins, cytoskeletal adaptor proteins and actin network filaments. Here we reveal how the integrity and dynamics of protrusive cores and adhesive rings are coordinated by the actomyosin apparatus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
150
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(181 citation statements)
references
References 48 publications
24
150
0
7
Order By: Relevance
“…However, recent structural analyses have revealed a more complex picture of podosome architecture. In particular, plaque proteins were shown to be assembled not in a continuous ring, but in several clusters that surround the core structure (van den Dries et al, 2013b). In addition, the core structure, being dependent on Arp2/3 complex activity (Kaverina et al, 2003;Linder et al, 2000a), has been shown to be surrounded by a layer of unbranched filaments (Akisaka et al, 2008;Luxenburg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent structural analyses have revealed a more complex picture of podosome architecture. In particular, plaque proteins were shown to be assembled not in a continuous ring, but in several clusters that surround the core structure (van den Dries et al, 2013b). In addition, the core structure, being dependent on Arp2/3 complex activity (Kaverina et al, 2003;Linder et al, 2000a), has been shown to be surrounded by a layer of unbranched filaments (Akisaka et al, 2008;Luxenburg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence thus suggest the presence of unbranched actin filaments at podosomes: (i) the identification of connecting cables that mediate contact between individual podosomes (Burgstaller and Gimona, 2005;Luxenburg et al, 2007), (ii) the observed contractility of individual podosomes (Labernadie et al, 2014(Labernadie et al, , 2010van den Dries et al, 2013a), which is probably based on the presence of unbranched actin filaments (Akisaka et al, 2008;Luxenburg et al, 2007), (iii) the presence of proteins such as myosin IIA (also known as MYH9) and supervillin (Bhuwania et al, 2012) that regulate actomyosin contractility, thus necessitating the presence of unbranched F-actin, (iv) the presence of the formin FMNL1, a regulator of unbranched F-actin, at podosomes (Mersich et al, 2010), and (v) as revealed by proteomic data, the presence of further formin isoforms in podosome-enriched cell fractions from macrophages (Cervero et al, 2012). Collectively, these findings indicate, in addition to Arp2/3 and associated proteins, the likely presence of regulators of unbranched filaments at podosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Actomyosin contractility is not required for podosome stability or the presence and recruitment of the tension-sensitive molecules vinculin and zyxin. 31 Also, integrin ligation appears redundant for podosome formation, as podosomes rapidly form on uncoated substrates and in the absence of ligandcontaining serum in Src-transformed fibroblasts and monocyte-derived DCs. 2,39 Moreover, REF52 fibroblasts have recently been shown to form podosomes on fluid Arg-Gly-Asp (RGD) peptide-lipid surfaces, demonstrating that podosomes indeed form in the absence of traction forces.…”
Section: Balancing Forces Within Podosomesmentioning
confidence: 99%
“…This is supported by our observation that the levels of the tension-sensitive components vinculin and zyxin oscillate in harmony with the actin core, while the levels of the tension-insensitive components are relatively stable. 31 Future studies should directly determine whether tension within the filamentous actin is indeed built up during podosome core growth or myosin IIA-mediated contraction. To fully support this model, the presence of a linkage between the central protruding core and the surrounding adhesive module is essential.…”
Section: Balancing Forces Within Podosomesmentioning
confidence: 99%
See 1 more Smart Citation